Komunitas ikan karang di perairan karang Pulau Weh, Sabang, Provinsi Aceh - Isa Nagib Edrus; Tri Aryono Hadi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2020)
Abstract. Prolonged coral reef damages due to natural and anthropogenic factors may lead to fish habitat changes. The habitat alteration will make the necessary study of fish community structures. This study was conducted in the 12 stations of the Weh Island reef waters. The purpose of this study is to provide baseline data for monitoring activities in the future. The study objective is to identify the reef fish community structures in terms of diversity, species composition, density, and biomass. Methods used was belt transect and visual census within transect areas of 350 m2. The results showed that there were at least 126 species of reef fishes with 18 families included in the fishing targeted group and the indicator fish group. Those respectively consisted of 23 corallivorous species, 36 herbivorous species, 53 carnivorous species and 14 zooplantivorous species. Their species number, density and biomass were varied among transect sites. The dominant species of corallivores were Hemitaurichthys zoster, Chaetodon guttatissimus, Chaetodon colare, Chaetodon trifasciatus, Forcipiger flavissimus, Chaetodon vagabundus, Chaetodon meyeri, Chaetodon kleinii, Heniochus singularis, and Heniochus pleurotaenia. The dominant species of herbivores were Acanthurus leucosternon, Ctenochaetus striatus, Acanthurus tristis, Ctenochaetus truncatus, Zebrasoma scopas, Chlorurus sordidus, Acanthurus triostegus, Scarus niger, Scarus ghobban and Acanthurus auranticavus. The dominant species of carnivores were Pempheris vanicolensis, Odonus niger, Mulloidichthys vanicolensis, Scolopsis ciliatus, Parupeneus barberinus, and Scolopsis bilineatus. The dominant spcies of zooplanktivores were Pterocaesio tile, Caesio xanthonotus, Sargocentron caudimaculatum, Myripristis berndti, Caesio caerulaurea, Pterocaesio randalli, Pterocaesio chrysozona, Caesio varilineatus andMyripristis kuntee. Species diversity of fish indicator and target fishes are relatively high. Among of the dozen study sites that have excellent conditions of diversity, composition, density and biomass are three location only.Keywords: Reef fish, community structures, Weh Island, Provinsi Aceh. Abstrak. Perubahan habitat ikan dapat terjadi sebagai akibat kerusakan terumbu karang yang berkepanjangan oleh sebab faktor-faktor alami dan kegiatan manusia. Perubahan habitat seperti ini mendorong kepada suatu kebutuhan penelitian struktur komunitas ikan karang. Lokasi Penelitian ini dilakukan di 12 stasiun pada perairan karang pulau Weh. Sasaran penelitian adalah untuk menyediakan data dasar bagi dalam kaitannya dengan kegiatan-kegiatan pemantauan dikemudian hari. Tujuan penelitian untuk mengindentifikasi struktur komunitas ikan karang berkaitan dengan parameter keanekaragaman, komposisi jenis, kepadatan individual dan biomassa. Metode yang digunakan adalah transek sabuk dan sensus visual dalam area transek seluas 350 m2. Hasil penelitian menunjukkan bahwa didapat 126 jenis ikan karang yang mewakili 18 suku yang termasuk kelompok ikan karang target dan ikan indikator. Jenis-jenis tersebut masing-masing terdiri dari 23 species koralivora, 36 species herbivora, 53 species karnivora dan 14 species zoopanktivora. Jumlah jenis, kepadatan dan biomassanya ditemukan bervariasi antara lokasi transek. Jenis yang mendominasi koralivora adalah Hemitaurichthys zoster, Chaetodon guttatissimus, Chaetodon colare, Chaetodon trifasciatus, Forcipiger flavissimus, Chaetodon vagabundus, Chaetodon meyeri, Chaetodon kleinii, Heniochus singularis, danHeniochus pleurotaenia. Jenis yang mendominasi herbivora adalah Acanthurus leucosternon, Ctenochaetus striatus, Acanthurus tristis, Ctenochaetus truncatus, Zebrasoma scopas, Chlorurus sordidus, Acanthurus triostegus, Scarus niger, Scarus ghobban dan Acanthurus auranticavus. Jenis yang mendominasi karnivora adalah Pempheris vanicolensis, Odonus niger, Mulloidichthys vanicolensis, Scolopsis ciliatus, Parupeneus barberinus, dan Scolopsis bilineatus. Jenis yang mendominasi zooplanktivora adalah Pterocaesio tile, Caesio xanthonotus, Sargocentron caudimaculatum, Myripristis berndti, Caesio caerulaurea, Pterocaesio randalli, Pterocaesio chrysozona, Caesio varilineatus dan Myripristis kuntee. Keanekaragaman jenis ikan indikator dan ikan karang target relatif tinggi. Di antara 12 lokasi penelitian yang terbaik dalam hal keragaman, komposisi, kepadatan dan biomassa hanya dijumpai pada tiga lokasi saja. Kata Kunci: Ikan karang, struktur komunitas, Pulau Weh Island, Provinsi Aceh.